Validitas Isi Alat Ukur Dukungan Sosial Melalui Expert Judgement pada Mahasiswa Terapi Wicara - Permatasari, Aprilia Ayu; Purwandari, Eny (Politeknik Kesehatan Kemenkes Surakarta, 2025)
Background: Speech Therapy students face high academic and clinical pressures, requiring social support as a protective factor to maintain psychological well-being and support their academic success. Objectives: This article aims to assess the content validity of a social support instrument specifically designed for Speech Therapy students. Methods: This study used a quantitative descriptive method. Validation was conducted using an expert judgement approach. The validation process involved assessment using a 5-point Likert scale. Data analysis used Aiken’s V and Content Validity Index (CVI). Results: The analysis showed that three items did not meet the Aiken’s V threshold (0.75) and required revision. The s-CVI value of 0.86 indicates that the instrument has high content validity overall. Conclusion: This study concludes that the developed measurement tool is suitable for use in academic and clinical contexts, with revisions to some items that are not yet valid. Keywords: content validity, expert judgement, social support, students, Aiken’s V, CVI